ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI SWEDISH FOOT MASSAGE DENGAN TINGKAT KESADARAN (LEVEL OF CONSCIOUSNESS) PADA PASIEN PERNURUNAN KESADARAN DI ICU RS BHAYANGKARA T.K. I R. SAID SUKANTO - Stephanie Ester Rosalia Sitorus (2022)
The ICU treats patients with reduced consciousness, whether mechanically ventilated or not. Unconsciousness itself is an unconscious state of oneself and the environment that can be physiological or pathophysiological. One of the modalities of therapy that can be given as an intervention for patients with decreased consciousness is Massage Therapy. Swedish massage therapy is manipulation of body tissues by doing massage using five basic movements, including effleurage, petrisage, friction, tapotement and vibration. The innovation intervention was carried out on patients managed in the ICU room at Bhayangkara Hospital TK.I R. Said Sukanto with a medical diagnosis of HIE (Hypoxic Ischemic Encephalopathy), Respiratory Failure on Ventiation, History of Abdominal Trauma and AKI. The implementation of the innovation intervention shows a positive impact on the level of patient awareness. although in resume patients there is no worsening. however, significant improvement was seen in the managed patients who were able to move their eyes.